Whole-brain metallomic analysis of the common marmoset (Callithrix jacchus). Issue 4 (1st March 2017) - Knauer, B.; Majka, P.; Watkins, K. J.; Taylor, A. W. R.; Malamanova, D.; Paul, B.; Yu, Hsin-Hao; Bush, A. I.; Hare, D. J.; Reser, D. H.
Abstract : This work represents the first whole-brain LA-ICP-MS metallomic map of a non-human primate species. Abstract : Despite the importance of transition metals for normal brain function, relatively little is known about the distribution of these elemental species across the different tissue compartments of the primate brain. In this study, we employed laser ablation-inductively coupled plasma-mass spectrometry on PFA-fixed brain sections obtained from two adult common marmosets. Concurrent cytoarchitectonic, myeloarchitectonic, and chemoarchitectonic measurements allowed for identification of the major neocortical, archaecortical, and subcortical divisions of the brain, and precise localisation of iron, manganese, and zinc concentrations within each division. Major findings across tissue compartments included: (1) differentiation of white matter tracts from grey matter based on manganese and zinc distribution; (2) high iron concentrations in the basal ganglia, cortex, and substantia nigra; (3) co-localization of high concentrations of iron and manganese in the primary sensory areas of the cerebral cortex; and (4) high manganese in the hippocampus. The marmoset has become a model species of choice for connectomic, aging, and transgenic studies in primates, and the application of metallomics to these disciplines has the potential to yield high translational and basic science value.